Effect of PAO-based γ-Fe2O3 and surfactant concentration on viscosity characteristic - Nikmat Leong, Siti Asma’; Mohd Samin, Pakharuddin; Idris, Ani; Azizul, Muhamad Asri; Misran, Effaliza (Trans Tech Publications, 2013)
This is a preliminary study on the viscosity characteristics of polyalphaolefin (PAO)- based γ-Fe2O3 under zero magnetic fields. By varying the concentration of magnetic nanoparticles (MNPs), PAO-based γ-Fe2O3 with different concentrations were synthesized by co-precipitation method. The effect of this factor on the viscosity characteristic of γ-Fe2O3 (< 30 nm) was investigated on the basic of a series of rheological measurement. The use of oleic acid (OA) as a coating agent and surfactant was also investigated by varying its concentration. The results show the concentration of MNPs and the amount of OA has obvious effect on viscosity characteristics of PAO-based γ-Fe2O3. In the case of comparison between the concentrations of MNPs, higher concentration of MNPs increased the viscosity of the PAO-based γ-Fe2O3 and exhibit nearly Newtonian behavior. The large amount of OA also exhibits the increment on viscosity characteristic of MNPs. The experimental data were compared with the Bingham and Casson model and the results revealed that the rheology of the polyalphaolefin (PAO)-based γ-Fe2O3 fitted the Casson model better.